2018
DOI: 10.1186/s12960-018-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of workplace respect and violence on nurses’ job satisfaction in Ghana: a cross-sectional survey

Abstract: BackgroundStudies have established the negative effects of workplace disrespect and violence on the personal and professional well-being of nurses. In spite of this, only a few have directly investigated the effects of these issues on nurses’ job satisfaction. In Africa, research on nurses’ job satisfaction continues to focus largely on economic factors. The aim of this paper was, therefore, to investigate the impact of the non-economic factors of workplace violence and respect on the job satisfaction levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 53 publications
4
46
1
Order By: Relevance
“…The job satisfaction of nurses in our sample was moderate, whereas other studies have reported that nurses in their samples had moderate or low job satisfaction (Boafo, ; Kantek & Kartal, ; Sansoni et al, ). Nevertheless, as in the findings of studies conducted in the United States (Brown et al, ; Hudgins, ; Matos, Neushotz, Griffin, & Fitzpatrick, ) and Singapore (Zheng et al, ), our results indicated a positive relationship between job satisfaction and the resilience of nurses.…”
Section: Discussioncontrasting
confidence: 81%
“…The job satisfaction of nurses in our sample was moderate, whereas other studies have reported that nurses in their samples had moderate or low job satisfaction (Boafo, ; Kantek & Kartal, ; Sansoni et al, ). Nevertheless, as in the findings of studies conducted in the United States (Brown et al, ; Hudgins, ; Matos, Neushotz, Griffin, & Fitzpatrick, ) and Singapore (Zheng et al, ), our results indicated a positive relationship between job satisfaction and the resilience of nurses.…”
Section: Discussioncontrasting
confidence: 81%
“…The findings also revealed that respect in organizations has a positive impact on employees' job satisfaction. These findings are consistent with the argument of Spector (1997, p.2) that people deserve to be treated with respect and job satisfaction is to some extent a reflection of good treatment and with the findings of the studies of Boafo (2018), Gardner (2008), Laschinger (2004), McGuire, Houser, Jarrar, Moy and Wall (2003), Quin and Wang (2012) and Society for Human Resource Management (2015;2016;.…”
Section: Resultssupporting
confidence: 89%
“…The current findings have valuable implications for nurse managers. Our study shows that mistreatment by patients is significant in lowering nurses' job satisfaction and increasing their turnover intention while previous study showed that the safe work environments which are devoid of violence may enhance nurses' job satisfaction [81]. One strategy would be to take steps to prevent mistreatment by patients from occurring in the first place.…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 58%